2017
DOI: 10.1016/j.ejon.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Hoping to reach a safe haven - Swedish families' lived experience when a family member is diagnosed with breast cancer

Abstract: Families experience an unmet need of information and support, which implies that healthcare professionals may want to acknowledge and include the family already at the time of diagnosis in order to help them endure and cope with the distressing experience and thus increase their wellbeing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 177 publications
(201 reference statements)
0
19
0
Order By: Relevance
“…Previous studies have reported that in the home-setting, caregivers are often responsible for providing treatment decision-making, symptom management, physical as well as emotional support [13,14]. Traditionally, caregiving has also been described in terms of the functional status of the patient [15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that in the home-setting, caregivers are often responsible for providing treatment decision-making, symptom management, physical as well as emotional support [13,14]. Traditionally, caregiving has also been described in terms of the functional status of the patient [15].…”
Section: Introductionmentioning
confidence: 99%
“…The burden of breast cancer caregiving includes emotional distress, financial burden, physical stress, and fear of uncertainty among caregivers [11][12][13]. Furthermore, the advanced stage disease presentation, a hallmark of this disease in LMICs, can result in increased psychosocial morbidity, poor physical health, and overall poor quality of life among caregivers [6,10,11,14].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Studies have shown that hope is an important construct for breast cancer patients to cope with the associated stressors and difficulties associated with the disease. 5,6 Hope is defined as the perceived capability and motivation to pursue and achieve the desired goals. 7 Research has found hope to be an important factor for maintaining a commitment to favorable goals and coping skills in women with breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Research has revealed that women with breast cancer can report a range of negative responses following diagnosis that include anger, anxiety related to death and fear of mastectomy, psychological distress, and self‐imposed social devaluation that may lead to feelings of hopelessness . Studies have shown that hope is an important construct for breast cancer patients to cope with the associated stressors and difficulties associated with the disease . Hope is defined as the perceived capability and motivation to pursue and achieve the desired goals .…”
Section: Introductionmentioning
confidence: 99%